Determination of Captopril Drug by Application of 1,10-Phenanthroline in the Spectrophotometric Technique - ANTAKLI, SAAD; SARKIS, NAZIRA; KABAWEH, MOHAMAD (Asian Journal of Chemistry, 2010)
We carried out a new spectrophotometric method in order to determine captopril drug which is used as antihypertensive in tablet form. The method is based on the reduction of Fe3+ to Fe2+ by captopril, the resulting Fe2+ reacts with 1,10-phenanthroline to give a soluble orange-red complex in acidic medium. The maximal absorption is at the wavelength 510 nm. The linear relationship between the absorbance and the concentration of captopril was in the range of 1-35 mg/L with a correlation coefficient R2 = 0.999. The detection limit is 1 mg/L, the molar absorption coefficient is 11865 L mol-1 cm-1. This new method has offered a determination of captopril drug without any interference with excipients or hydrochlorothiazide either in raw material or in tablets indirectly with a high accuracy and an authenticity for the analytical results.